PEDAGOGICAL PSYCHOLOGY IN THE RESEARCH ACTIVITIES OF STEFAN BALEY - PODOLIAK , MYKHAILO (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article is dedicated to the revealing of the problem of pedagogical psychology in research activities and works of Ukrainian and Polish researcher, pedagogue, psychologist, philosopher Stefan Baley (1885-1952). The relevance of the theme is conditioned by the active reforming processes of Ukrainian educational system, in which ideas of the scholar can be widely used as well as his thoughts, ideas and research of child psyche. The article gives biographical data of the scholar and emphasizes his field of work as well as main works. The principles, subject and aims of pedagogical psychology according to Stefan Baley are presented in the article. The article analyses the notion of education and educational relations according to the researcher as well as the process of education and its types, namely: analytic and empiric education, systematic and global education. The problem of a child education in a group is presented in the article i.e. school class. The author emphasized the actuality and expediency of practical usage of ideas and research activities of Stefan Baley at the current stage of Ukrainian school system reforming, according to the results of comparison between the problematics of Stefan Baleys' research activities in the sphere of pedagogical psychology and K. Seifert and R. Sutton.